Pengaruh Pengambilan Keputusan Kepala Madrasah Terhadap Kinerja Guru MA Unggulan Mukhtar Syafaat Blokagung Tegalsari Banyuwangi - Moh. Imam Khaudli; Nur Shofa Ulfiyati; Nur Hasan Asngari (Jurnal Manajemen Pendidikan Islam Darussalam (JMPID), 2020)
The research aims to : (1) how is the decision making of madrasah head in MA Featured Mukhtar Syafaat Blokagung Tegalsari Banyuwangi 2018/2019 Academic Year (2) How is the performance of teachers in MA Featured Mukhtar Intermediate Blokagung Tegalsari Banyuwangi Learning Year 2018/2019 (3) Is the influence of madrasah headmasters' decision making on the performance of the MA Supreme Teacher Mukhtar Intercession Blokagung Tegalsari Banyuwangi 2018/2019 Academic Year. This research uses quantitative descriptive method with the product moment technique. The population of this research is educator in MA Featured Mukhtar Syafaat Blokagung educator is numbering 19. After analyzing the data collected, it was found that (1) madrasah headmasters' decision making in MA Featured Mukhtar Syafaat Blokagung was classified as very good. (2) the performance of teachers in MA Featured Mukhtar Syafaat Blokagung very good. (3) the results of the influence of madrasah headmasters' decision making on the performance of teachers in MA Featured Mukhtar Syafaat Blokagung there. the influence of madrasah headmasters' decision making on the performance of MA Supreme Master Mukhtar Syafaat Blokagung of 78.7%.